Trace Element (Pb, Cd, and As) Contamination in the Sediments and Organisms in Zhalong Wetland, Northeastern China. Issue 4 (18th May 2016) - Luo, Jinming; Ye, Yajie; Gao, Zhongyan; Wang, Yongjie; Wang, Wenfeng
ABSTRACT: This study examined Tessier's fractions of Pb, Cd, and As in the sediments and their potential toxic effects on four aquatic animals, i.e., Enchytraeus of Lumbricidae, Cipangopaludina chinensis of Viviparidae, Cybister japonicus Sharp of Dytiscidae, and Perccottus glenii Dybowski of Odontobutidae in Zhalong Wetland, Northeastern China. Results show that Cd poses a high risk to the biota in Zhalong Wetland. The geo-accumulation indices indicate that the region only has background concentrations of As, although it is slightly polluted by Pb and is seriously polluted by Cd. The exchangeable fraction receives minor contributions from these metals: 0.8% for Pb, 2.8% for Cd, and 4% for As. Three reed organs and four aquatic animal groups contain detectable concentrations of Pb, Cd, and As, with the following order of increasing concentrations: stem < rhizome < root < Viviparidae < Odontobutidae < Dytiscidae < Lumbricidae. Relatively low bioaccumulation factor (BAF) of As occurred in four aquatic organisms, whereas significantly higher BAFs of Pb and Cd were found in the earthworm than other aquatic organisms ( P < 0.05). The earthworms (Enchytraeus of Lumbricidae) were recommended to be used as a suitable indicator for Pb, Cd, and As toxic risk level in this region.